(untitled) (Per Musi, 2012)
Motivation can interfere with the music profession, especially by the constant need for instrumental practice. Thus, we sought to identify the factors related to motivation for developing the work of 22 musicians from an unprofessional orchestrain southern Brazil. In general, one can say that the musicians are motivated to carry out the work.